VOILA on the LUVMI-X Rover: Laser-Induced Breakdown Spectroscopy for the Detection of Volatiles at the Lunar South Pole - David S. Vogt; Susanne Schröder; Lutz Richter; Michael Deiml; Peter Weßels; Jörg Neumann; Heinz-Wilhelm Hübers (Sensors, 2022)
The project Lunar Volatiles Mobile Instrumentation—Extended (LUVMI-X) developed an initial system design as well as payload and mobility breadboards for a small, lightweight rover dedicated for in situ exploration of the lunar south pole. One of the proposed payloads is the Volatiles Identification by Laser Analysis instrument (VOILA), which uses laser-induced breakdown spectroscopy (LIBS) to analyze the elemental composition of the lunar surface with an emphasis on sampling regolith and the detection of hydrogen for the inference of the presence of water. It is designed to analyze targets in front of the rover at variable focus between 300 mm and 500 mm. The spectrometer covers the wavelength range from 350 nm to 790 nm, which includes the hydrogen line at 656.3 nm as well as spectral lines of most major rock-forming elements. We report here the scientific input that fed into the concept and design of the VOILA instrument configuration for the LUVMI-X rover. Moreover, we present the measurements performed with the breadboard laboratory setup for VOILA at DLR Berlin that focused on verifying the performance of the designed LIBS instrument in particular for the detection and quantification of hydrogen and other major rock forming elements in the context of in situ lunar surface analysis.